'Transnational civil dis/obedience' in the Danish family unification dispute. (10th March 2014) - Wagner, Rikke
<x content-type="archive" xml:space="preserve">Abstract</x> This article develops a concept of transnational civil dis/obedience. It provides a framework for interpreting and evaluating practices of cross-border movement by citizens and migrants, who mobilize international or supranational law to sidestep and challenge domestic rules deemed illegitimate. Such acts are made possible by, but also enact, complex, overlapping and competing legal orders in Europe and elsewhere. In contrast to analyses stressing the private and market-based nature of these actions, the conceptual lens introduced here draws out their potentially civic and political character. To construct and illustrate my argument, I engage with an in-depth case study of EU citizenship and cross-border movement in the area of marriage migration, where individual liberty and political membership are fiercely contested. The paper draws on narrative interviews with Danish-international couples who in response to Denmark's restrictive family unification rules have used EU-law to protest against what they see as unjust interference in their private lives.